2015
DOI: 10.1016/j.bjorl.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance and swallowing: critical literature review

Abstract: The main purpose of the manuscripts that investigate the swallowing process through fMRI were: to characterize swallowing in different pathologies; to compare swallowing in different age groups; to describe brain activation in different stimulation conditions. These studies indicate multiple cortical regions involved in swallowing control. Overall, the studies indicate that fMRI is a non-invasive and quantitative method that allows the investigation of characteristics that are quite often not clinically visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…not applicable. 45 . Neuroimaging studies show that the motor cortex and the basal ganglia as extrapyramidal motor network are involved in the central control of swallowing [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…not applicable. 45 . Neuroimaging studies show that the motor cortex and the basal ganglia as extrapyramidal motor network are involved in the central control of swallowing [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Swallowing is a coordinated physiological process, involving complex neuromuscular interactions (Ertekin and Aydogdu, 2003). Extensive research has shown that the swallowing network includes the brain regions of the primary sensorimotor system, supplementary motor area (SMA), insula, cingulate cortex, IFG, IPL, temporal lobe, precuneus, cerebellum, and brain stem (Hamdy et al, 1999a;Lang, 2009;Soros et al, 2009;Lima et al, 2015;Toogood et al, 2017). When any area of the swallowing network is damaged, dysphagia occurs (Domenech and Kelly, 1999;Gonzalez-Fernandez and Daniels, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional rTMS stimulation site is roughly determined by locating the hot-spot area of a single swallowing muscle, e.g., the mylohyoid or pharyngeal muscle (Khedr et Numerous previous studies have shown that fMRI is a useful imaging technique for investigating changes in neuronal activity in the brain during swallowing, including motor, sensory and autonomic components (Lima et al, 2015). We believe that peak voxels activated by saliva swallowing in fMRI scans could be better stimulation sites than those identi ed by traditional route.…”
Section: Brain Areas Of Saliva Swallowing Task Fmri Activation In Exp...mentioning
confidence: 99%
“…Mylohyoid is only one of the representative muscles involved in the oral phase of swallowing. Swallowing is a complex sensory-motor process(Lima et al, 2015), one single muscle cannot represent the entire swallowing process. Functional brain imaging may be able to detect the neuronal patterns that govern this complicated sensory-motor process, elucidating the key neural mechanisms(Lima et al, 2015).…”
mentioning
confidence: 99%